2001
DOI: 10.1097/00001756-200101220-00022
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte growth factor prevents ischemia-induced delayed neuronal death in the hippocampal CA1 field of the gerbil brain

Abstract: Fibroblast growth factors (FGFs) are polypeptides with various biological activities in vivo and in vitro, and their receptors are expressed in the widespread and specific neuronal populations of the brain. In this study, we asked whether keratinocyte growth factor (KGF), one of the FGF superfamily, would express in the brain, and have neuroprotective against ischemic brain injury. In situ hybridization analysis revealed that intense silver grains for KGF mRNA are observed in the neuronal cells of the cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Recent studies have shown an anti-apoptotic effect of KGF on various tissues such as epidermal cells [29], neural cells [30] and hepatocytes [31]. In this study KGF could have exerted such a role on transplanted cells in the early days after transplantation, a time at which some loss of tissue is known to occur [32].…”
Section: Effect Of Kgf On Beta Cell and Ductal Cell Proliferationmentioning
confidence: 72%
“…Recent studies have shown an anti-apoptotic effect of KGF on various tissues such as epidermal cells [29], neural cells [30] and hepatocytes [31]. In this study KGF could have exerted such a role on transplanted cells in the early days after transplantation, a time at which some loss of tissue is known to occur [32].…”
Section: Effect Of Kgf On Beta Cell and Ductal Cell Proliferationmentioning
confidence: 72%
“…OPN binding to α4β1 integrin has been implicated in the organization of endothelial cells in the developing vasculature, the extravasation of immune cells into tissues, and the emigration of neuroblasts[37]. Fibroblast growth factor-7 (FGF7 or KGF), which was increased 173-fold in our study, is known to mediate cell proliferation and motility, protect against cell death,[38] and has been shown to limit ischemia-induced neuronal death[39]. We also found a 44-fold increase in olfactomedin-1 (Olfm1), which has been implicated in neuronal differentiation, axon extension and cell survival[40].…”
Section: Discussionmentioning
confidence: 96%
“…We first investigated the effect of KGF in the prevention of b-cell apoptosis in the pancreas of STZ/KGF rats. Anti-apoptotic effects of KGF on various tissues such as epidermal cells (Jeschke et al 2002), neural cells (Sadohara et al 2001), and hepatocytes (Senaldi et al 1998) have been described in numerous studies. It is known that STZ induces b-cell death partly by stimulation of apoptosis (Yamamoto et al 1981, Cardinal et al 2001.…”
Section: Discussionmentioning
confidence: 99%